Application of Lemongrass Oil in Chitosan as Antimicrobial During Storage of Crystal Guava Fruit - Syarifah Meutiah Eka Sari; Irma Suparto; Wulan Tri Wahyuni (Institut Pertanian Bogor, 2025)
Guava crystal is a fruit that has a high selling value. One of the obstacles to marketing crystal guava fruit is the fast decay process. Many factors cause fruit to rot quickly, including microbial contamination post-harvesting. This study evaluates the effectiveness of adding lemongrass oil in chitosan coatings to protect crystal guava from microbiological damage during storage. The fruit is coated with 1% chitosan and added to lemongrass oil according to the treatment. The study used a completely randomized design with three replications. The treatment tested included 0.0, 0.1, 0.3, and 0.5% lemongrass oil. The content of lemongrass oil compounds was analyzed using gas chromatography-mass spectroscopy (GC-MS). The antibacterial test was carried out using the disc method. The parameters observed were the total plate count and total fungal count of crystal guava fruit on days 0, 3, 6, 9, 12, 15, and 18 after storage. GC-MS analysis showed that the main content of lemongrass oil is two isomers of citral, i.e., neral (38.54%) and geranial (39.26%). The results showed that the total fungal and plate count increased during storage. Chitosan coating with lemongrass oil more effectively inhibits Staphylococcus aureus than Escherichia coli. Adding 0.3% and 0.5% lemongrass oil in chitosan could restrain the rate of microbes in crystal guava until the 18th day after storage. Chitosan treatment with 0,3% lemongrass oil is recommended to be the best treatment for applying on crystal guava. Keywords: citral, GC-MS, Psidium guajava L., total plate count, total fungal count